2018
DOI: 10.3390/mti2020011
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Observation and Classification of People Engaged in Problem Solving: Application to Chess Players

Abstract: In this paper we present the first results of a pilot experiment in the interpretation of multimodal observations of human experts engaged in solving challenging chess problems. Our goal is to investigate the extent to which observations of eye-gaze, posture, emotion and other physiological signals can be used to model the cognitive state of subjects, and to explore the integration of multiple sensor modalities to improve the reliability of detection of human displays of awareness and emotion. Domains of appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The tasks were presented with the subject alternately playing black or white. Full results with eye-gaze and fixation are discussed in [13]. Here we concentrate on observations of emotion.…”
Section: Results From the First Pilot Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks were presented with the subject alternately playing black or white. Full results with eye-gaze and fixation are discussed in [13]. Here we concentrate on observations of emotion.…”
Section: Results From the First Pilot Experimentsmentioning
confidence: 99%
“…As a pilot study, we observed expert chess players engaged in solving problems of increasing difficulty [13]. During the study, data were recorded from all sensors (Kinect 2, Webcam, Screen capture, user clicks, Tobii-Bar) using the RGBD Sync SDK from the Mobile RGBD project.…”
Section: Introductionmentioning
confidence: 99%
“…The reported results may hide that there are still rooms for improvement, the underlying bottleneck of these researches on chess remaining the amount of available data. The available recordings of eye tracking data in chess context [Guntz et al, 2018] represent a huge amount of work and hours of data. Nevertheless, they contain few configurations and around 30 players recorded in actual chess problem solving tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This data was acquired for an experimentation on observing and interpreting subjects in problem solving tasks (chess in particular) through multimodal observations (eye tracking, posture, facial emotion, etc.) [Guntz et al, 2018].…”
Section: Visual Attention In Chessmentioning
confidence: 99%
See 1 more Smart Citation